Grape (Vitis vinifera L.) phytochemicals and their biochemical protective mechanisms against leading pathologies. (30th March 2023) - Majeed, Usman; Shafi, Afshan; Majeed, Hamid; Akram, Kashif; Liu, Xuehua; Ye, Jianming; Luo, Yane
Graphical abstract: Highlights: Quercetin and catechin have excellent nutritional as well as therapeutic value. Kaempferol and resveratrol have shown excellent anti-proliferative activities via P13K/Akt and MAPK blockage. The anti-proliferative mechanism also involved reduction in levels of NRF2 and NFκB. Cardio protection involved low oxidation of LDL and HDL proteins. Grape polyphenols inhibit α-glucosidase to control diabetes. Abstract: The intake of herbal dietary constituents, mostly fruits and vegetables, have been considered well-known to prevent pathologies (degenerative diseases). Consumer awareness/concern regarding a balanced diet has increased their importance in the food chain. Grapes ( Vitis vinifera L .), being native to the Mediterranean region, central Europe, and southwest Asia, is a rich source of nutritive (sugar, vitamins, minerals) and non-nutritive/therapeutic or functional bioactive compounds like quercetin, resveratrol and epigallocatechin-3-gallate that could synergistically help in health promotion. Their disease prevention mechanisms are free radical scavenging, DNA damage repair, and modulation of gene expression in proliferation, metabolism, cell survival, and antioxidant defense. This review provides an excellent summary of grape phytochemicals in vivo molecular mechanisms that lead to health promotion by avoiding oxidative stress-related pathologies like cancer, neurodegeneration, metabolic syndrome, inflammation and cardiovascular diseases. Grape intake-driven disease-preventing mechanism/targets could help to synchronize for an improved efficacy in human pathologies.